Pragmatisme Partai Nasional Demokrat dalam Sistem Pemilu Terbuka - Masad Masrur; Felita Purnomo; Silvia Arviana; Hilda Yunita Wono (JCommsci - Journal Of Media and Communication Science, 2022)
The National Democratic Party's strategy in facing the 2019 Election with an open proportional representation system is to recruit celebrities as voters. Their placement as candidates for state administrators risks injuring the substance and objectives of democracy, because candidates for state administrators must have certain ideologies and competencies as well as the replacement of ideological cadres by celebrities. This qualitative research uses the literature study method for data collection. The purpose of this study is to find out the pragmatism of the national democratic party in an open proportional electoral system. From the results obtained, political parties tend to leave ideological cadres rather than representing members and the wider community. The Nasdem Party finally saw that celebrities are part of professional actors who have the ability as celebrity politicians although in practice they play more roles as celebrity endorsers. Placement of celebrities as candidates for state administrators is a necessity for sales-oriented parties. However, it is necessary to consider the risks to the aims and substance of democracy.